Salvia species as nutraceuticals: focus on antioxidant, antidiabetic and anti-obesity properties - Fernandes Afonso, Andrea Luísa (2021)
Salvia plants belong to the Lamiaceae family and are recognized as being strongly aromatic, being widely used for different purposes in culinary or traditional medicine. These plants are well recognized as being rich in phenolic acids, flavonoids and terpenic compounds, which exhibit health-beneficial activities, protecting against oxidative and inflammatory-related diseases, such as diabetes and obesity. Because of these properties, phytochemicals from Salvia species have been investigated as health promoting agents, for application in distinct fields. However, the growing demand for natural products with possible uses and applications in industry requires scientific validation studies. This review consists of a compilation of relevant studies with an emphasis on the antioxidant, antidiabetic and anti-obesity properties of phenolic-rich extracts from Salvia plants.